Analysis of Students' Cognitive Ability in Solving Physics Problems on Parabolic Motion Material for Class XI Science at MAN 3 Bojonegoro - Zahrotin, Anis (Science Education and Application Journal, 2022)
This research is a survey research with quantitative descriptive data type carried out at MAN 3 Bojonegoro. The population in this study was all students of class XI IPA MAN 3 Bojonegoro with a total sample of 129 students who were divided into four classes. The background of the problem in this study is the low problem-solving ability of students in solving physics problems on parabolic motion material. The results showed that 73.13% of students were in the high category for the factual dimension and 67.24% of the students were in the high category for the conceptual dimension. Students still have difficulty in solving cognitive questions at the evaluation level (C5) and creating (C6) with 24% of respondents answering. On cognitive questions at the Application (C3) and Analysis (C4) levels, the success rate of answering students' questions correctly is at the level of 90% and 9 4 5%. This shows that learning in schools is by national education goals which put learning objectives on Parabolic Motion material at the C4 level. These results are expected to be a reference for Physics Teachers at MAN 3 Bojonegoro to improve the learning process in the realm of High Order Thinking.